Representation of depressive manifestations in pregnant women with the threat of abortion living in the Lugansk region - Iryna, Романенко (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the II Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to the representation of depressive manifestations in pregnant women with the threat of abortion living in the Lugansk region.